News Media Coverage of Environmental Challenges in Latin America and the Caribbean Mediating Demand, Degradation and Development (Palgrave Studies in Media and Environmental Communication, 2018)
This edited collection provides a unique survey of the ways in which news media organizations across Latin America and the Caribbean cover global, regional and local environmental issues and challenges. There is growing recognition within academia, governments, industries, NGOs and civil society about the importance of strategic communication and the news media in informing current societal and policy discussions about environmental issues. With this in mind, this volume explores the content of reporting as well as the structural and individual contests faced by media organizations and journalists, with a focus on the very unique political, social, cultural and environmental conditions that affect the countries individually. The book provides a survey of the most relevant and current environmental issues that have attracted public attention across the region and within countries in Latin America and the Caribbean in the first part of the 21st century. This volume will be of interest to students, instructors and researchers interested in Latin America and the Caribbean, media and the environment.